The antimicrobial spectrum of Xeroform®. Issue 6 (September 2017) - Barillo, David J.; Barillo, Anthony R.; Korn, Sarah; Lam, Kan; Attar, Paul S.
Graphical abstract: Highlights: Xeroform ® is a petrolatum-based fine mesh gauze containing bismuth tribromophenate. Certain bismuth compounds have antimicrobial activity. The antimicrobial spectrum of Xeroform ® remains largely unknown. We examined the in-vitro efficacy of Xeroform ® against 15 common burn pathogens. Xeroform has no intrinsic antimicrobial activity against common burn pathogens. Abstract: Introduction/background: Xeroform ® is a petrolatum-based fine mesh gauze containing 3% bismuth tribromophenate. Bismuth, similar to other metals, has antimicrobial properties. Xeroform ® has been used for decades in burn and plastic surgery as a donor site dressing and as a covering for wounds or partial thickness burns. Despite this, the antimicrobial spectrum of Xeroform ® remains largely unknown. We examined the in-vitro efficacy of Xeroform ® against common burn pathogens using zone-of-inhibition methodology in a commercial research facility. Methods/design: Pure strains of 15 common burn pathogens including Methicillin-resistant Staphylococcus aureus ( MRSA ), Methicillin-sensitive Staphylococcus aureus ( MSSA ), Staphylococcus epidermidis, Pseudomonas aeruginosa, Enterobacter cloacae, Escherichia coli, Candida albicans, Vancomycin resistant Enterococcus, Acinetobacter baumennii, Klebsiella pneumonia, Extended spectrum beta-lactamase producing Klebsiella, Beta hemolytic Streptococcus pyogenes, Proteus mirabilis, Serratia marcescens, and Salmonella enterica ssp . Enterica were inoculated at a strength of 10 6 –10 10 CFU/ml onto appropriate agar plates. A sterile 1 in 2 Xeroform ® square was placed in the center of each plate, and the Zone of Inhibition (ZOI) was measured following 18–24 h of incubation at 37 °C. A second bismuth pharmaceutical (bismuth subsalicylate, Pepto-Bismol ® ) was then tested using the same methodology against the same strains of MRSA, MSSA, E. coli, K. pneumonia and S. marcescens. Finally, 3% w/v bismuth tribromophenate in glycerol suspension was tested against 13 burn pathogens for antimicrobial activity independent of the Xeroform ® dressing by measure of Zone of Inhibition. Results/findings: For Xeroform ®, none of the fifteen pathogens had a measurable zone of inhibition on any plate. Bismuth subsalicylate showed a zone of inhibition for MSSA in 3 plates (mean of 47.2 mm), in one of three plates for MRSA (13.8 mm), and in one of three plates for S. marcesens (89.6 mm). There was no zone of inhibition seen for K. pneumonia or E. coli . Bismuth tribromophenate, when not bound to Xeroform ® showed activity against 12 of 13 pathogens. Conclusions/implications: While bismuth subsalicylate, and bismuth tribromophenate unbound to Xeroform ® demonstrate antimicrobial activity, it appears that Xeroform ® dressings do not. The utility of Xeroform ® in burn medicine may relate more to use as an impervious dressing than to antimicrobial effect. Donor sites are clean surgical wounds and clean partial thickness burns may have minimal colonization present. In such circumstances, an inactive and impervious dressing may be all that is necessary to promote wound healing.